Family farming in sub-Saharan Africa: Its contribution to agriculture, food security and rural development - Sam Moyo (International Policy Centre for Inclusive Growth (IPC-IG), 2016)
The persistent agrarian crisis facing sub-Saharan Africa (SSA) and the recent food price hikes have provoked greater urgency among governments, civil society actors and development agencies to identify public policies that can accelerate agricultural transformation towards achieving food security and nutrition, as well as sustainable and inclusive rural development. Considering that 75 per cent of the SSA population is involved directly or indirectly in farming and related employment, the strategic role of family farms in such a transformation is increasingly being recognised by key actors (FAO 2013; 2014). There is less agreement on the nature of and prospects for family farms in SSA, the scope of their contributions to agriculture, food security and rural development, and the measures required to address their most critical challenges. [...]
Keywords: 330; family farming; sub-Saharan Africa; contribution; agriculture; food security; rural development